An Integrated Approach to Teaching and Learning Law: The Use of Student Peer Mentor Groups to Improve the Quality of Student Learning in Contracts - Peter JM MacFarlane; Gordon Joughin (Legal Education Review)
Increasing student numbers and decreasing education funding threatens to perpetuate a number of significant, interrelated problems in undergraduate legal education. These problems are epitomised by the following characteristics of teaching and learning which we believe are not uncommon in Australian legal education: Teaching occurs in large classes (which are at their largest in the crucial first year). Students are given little opportunity for interaction, self-direction, cooperative learning, or for debating ideas among their peers. Students often feel alienated, conscious of their perceived “lack of knowledge” and, in spite of their obvious success in previous study, concerned about meeting the high expectations placed on them. Teaching methods centre on lectures as a focus for transmitting instrumental knowledge, supplemented by seminars or tutorials, which often develop into mini-lectures. Students constantly look to the academic for “answers” as to “what is the law”; they often commit the resulting information to memory and regurgitate it in examination scripts, before forgetting it. The students move on to the next year, often with their first love of learning lost. Legal educators are faced not only with these problems but also with growing demands to address issues concerning the quality of teaching and learning in their subjects. And while traditional methods such as the lecture and seminar continue to dominate undergraduate legal education, increasing use is being made of less traditional, more innovative teaching and learning methods, exemplified by the use of materials-based learning (using computers and other media), the development of real life as well as simulated clinical situations and the introduction of more active learning methods within the classroom. It was against this background of well recognised problems1 and the search for solutions, that the Contracts subject in the Queensland University of Technology’s LLB course was redesigned.2 This commitment to doing something about the problems outlined above coincided with a major review of the LLB curriculum, making the environment ripe for developing teaching and learning methods more appropriate for first-year law students. This paper reports on this redesign, first by considering the total teaching and learning environment of the subject and then by focusing on that aspect of the new environment which we consider unique to legal education in Australia — the student peer mentor group.